DNA Methylation Cancer Biomarkers: Translation to the Clinic - Locke, Warwick J.; Guanzon, Dominic; Ma, Chenkai; Liew, Yi Jin; Duesing, Konsta R.; Fung, Kim Y.C.; Ross, Jason P. (Frontiers in Genetics, 2019)
Carcinogenesis is accompanied by widespread DNA methylation changes within the cell. These changes are characterised by a globally hypomethylated genome with focal hypermethylation of numerous 5'-cytosine-phosphate-guanine-3' (CpG) islands, often spanning gene promoters and first exons. Many of these epigenetic changes occur early in tumorigenesis and are highly pervasive across a tumour type. This allows DNA methylation cancer biomarkers to be suitable for early detection and also to have utility across a range of areas relevant to cancer detection and treatment. Such tests are also simple in construction, as only one or a few loci need to be targeted for good test coverage. These properties make cancer-associated DNA methylation changes very attractive for development of cancer biomarker tests with substantive clinical utility. Across the patient journey from initial detection, to treatment and then monitoring, there are several points where DNA methylation assays can inform clinical practice. Assays on surgically removed tumour tissue are useful to determine indicators of treatment resistance, prognostication of outcome or to molecularly characterise, classify and determine the tissue of origin of a tumour. Cancer-associated DNA methylation changes can also be detected with accuracy in the cell-free DNA present in blood, stool, urine and other biosamples. Such tests hold great promise for the development of simple, economical and highly specific cancer detection tests suitable for population-wide screening, with several successfully translated examples already. The ability of circulating tumour DNA liquid biopsy assays to monitor cancer in situ also allows for the ability to monitor response to therapy, to detect minimal residual disease and as an early biomarker for cancer recurrence. This review will summarise existing DNA methylation cancer biomarkers used in clinical practice across the application domains above, discuss what makes a suitable DNA methylation cancer biomarker and identify barriers to translation. We discuss technical factors such as the analytical performance and product-market fit, factors that contribute to successful downstream investment, including geography, and how this impacts intellectual property (IP), regulatory hurdles and the future of the marketplace and healthcare system.